PUSAT PEMASARAN KOPI TORAJA DI MAKASSAR DENGAN PENDEKATAN ARSITEKTUR EKOLOGI - Nirhamullah Nirhamullah; Wasilah Wasilah (Nature: National Academic Journal of Architecture)
South Sulawesi is one area which is famous for agricultural products. One result is that the famous spice Coffee. A coffee plantation crops in South Sulawesi, especially in the districts of Tana Toraja promising. That is known by the name "Toraja Coffee" which is very popular coffee lovers in Indonesia and until foreign. Toraja coffee marketing center is a central place that serves as a principal activity to promote or market one type of beverage derived from the coffee processing plant of one of the areas in South Sulawesi, namely Tana Toraja. Building a public building in the field of industry will certainly have an adverse impact on the environment. To minimize environmental damage to the application of the concept of environmentally friendly is needed. Application of Architecture Ecology concept is a blend of environmental science and science-oriented architecture development model by taking into account the balance of the natural environment and the built environment. Eco Architecture serves as a means of education and analysis to achieve environmentally sound physical facilities, the planning done by Eko Architecture, it will manifest harmony between the physical facilities with Environment.